A Novel Hybrid Additive Manufacturing Methodology for the Development of Ti6Al4V Parts - Singh G.; Kumar S.; Sharma P. (My University, 2025)
The prime objective of the current investigation is to develop a methodology of hybrid additive manufacturing (HAM), which is an amalgamation of vat photopolymerization (VPP) based 3D printing and pressureless sintering, for the fabrication of Ti6Al4V parts for biomedical applications. In this study, the effect of a wide range of sintering temperatures (1200 to 1600 °C), heating rate (2 to 4 °C/min), and holding time (60 to 180 minutes) has been considered. Further, the effect of process variables on three responses, namely porosity, shrinkage, and compressive yield strength, are investigated. It is found that sintering temperature is the most significant process variable, followed by heating rate and holding time, influencing all three responses. With an increase in sintering temperature, porosity reduces while shrinkage and compressive yield strength increase. Further, fabricated specimens are characterized using XRD and EDS analysis. XRD analysis confirms the existence of both α and β-phases, and EDS analysis negates any possibility of significant contamination during sintering. Microstructure evolution from SEM micrographs suggests significant neck growth and densification, with fully connected pores, which ensures good bonding between powder particles. The present investigation’s outcome helps develop porous near-net shape complex parts for biomedical applications. Graphical Abstract: (Figure presented.) © ASM International 2023.